Week 96 results of a phase 3 trial of darunavir/cobicistat/emtricitabine/tenofovir alafenamide in treatment-naive HIV-1 patients. (1st April 2020) - Orkin, Chloe; Eron, Joseph J.; Rockstroh, Jürgen; Podzamczer, Daniel; Esser, Stefan; Vandekerckhove, Linos; Van Landuyt, Erika; Lathouwers, Erkki; Hufkens, Veerle; Jezorwski, John; Opsomer, Magda
Abstract : Background: Darunavir/cobicistat/emtricitabine/tenofovir alafenamide (D/C/F/TAF) 800/150/200/10 mg was investigated through 96 weeks in AMBER (NCT02431247). Methods: Treatment-naive, HIV-1-positive adults [screening plasma viral load ≥1000 copies/ml; CD4 + cell count >50 cells/μl) were randomized (1 : 1) to D/C/F/TAF ( N  = 362) or D/C plus emtricitabine/tenofovir-disoproxil-fumarate (F/TDF) ( N  = 363) over at least 48 weeks. After week 48, patients could continue on or switch to D/C/F/TAF in an open-label extension phase until week 96. Results: At week 96, D/C/F/TAF exposure was 626 patient-years (D/C/F/TAF arm) and 109 patient-years (control arm post switch), week 96 virologic suppression (viral load <50 copies/ml; FDA-Snapshot, from baseline) was 85.1% (308/362) (D/C/F/TAF) and 83.7% (304/363) (control). Week 96 virologic failure (viral load ≥50 copies/ml; FDA-Snapshot) was 5.5% (20/362) and 4.4% (16/363), respectively. No darunavir, primary protease inhibitor or tenofovir resistance-associated mutations (RAMs) were observed post baseline. In one patient in each arm, an M184I and/or V RAM was detected. Few adverse event-related discontinuations (3% D/C/F/TAF; <1% control post switch) and no deaths occurred on D/C/F/TAF. Improved renal and bone parameters were maintained in the D/C/F/TAF arm and observed in the control arm post switch. Increases in total-cholesterol/high-density-lipoprotein--cholesterol rtio at week 96 were +0.25 versus baseline (D/C/F/TAF) and +0.24 versus switch (control). Conclusion: At week 96, D/C/F/TAF resulted in high virologic response and low virologic failure rates, with no resistance development to darunavir or TAF/TDF. Bone, renal and lipid safety were consistent with known D/C/F/TAF component profiles. Control arm safety post switch was consistent with the D/C/F/TAF arm. AMBER week 96 results confirm the efficacy, high barrier to resistance and bone/renal safety benefits of D/C/F/TAF for treatment-naive patients. Abstract : Supplemental Digital Content is available in the text